Does an improved HDI trigger tourism outflows for China? New evidence from the ARDL cointegration approach - Ahsan Akbar; Farrukh Nawaz; Xie Hui; Irfan Ullah; Minhas Akbar; Veronika Zidova; Asokan Vasudevan (PLoS ONE, 2025)
Extant studies have predominantly focused on understanding the effects of inbound tourism on economic growth. At the same time, it ignores the key factors that promote outbound tourism in a country. Outbound tourism not only plays a crucial role in the sustainable development of the host country but also helps foster an understanding of cross-cultural similarities and differences, promoting goodwill towards the home country. It also provides an opportunity to experience the cuisine, weather, and working habits of different geographical locations. Therefore, this study aims to investigate the relationship between the Human Development Index and tourism outflows in the context of China. We use data from the period 1995–2020 to estimate the relationship between the Human Development Index (HDI) and tourism outflows. The short-run and long-run Autoregressive Distributed Lag (ARDL) results indicate that improving China’s Human Development Index (HDI) has a positive impact on tourism outflows. More precisely, a 1 unit increase in the HDI index will increase tourism outflow by 5.25%. Furthermore, the results of individual HDI show that life expectancy, per capita income, and education considerably promote China’s tourism outflows. Policy prescriptions are outlined regarding the spillover effects of China’s human development on the tourism-led economic growth of recipient countries.